Does Higher Education Enhance Migration? - Mika Haapanen; Petri Böckerman (Institute for the Study of Labor (IZA), 2013)
This paper examines the causal impact of education on within-country migration. A major higher education reform took place in Finland in the 1990s. It gradually transformed former vocational colleges into polytechnics and expanded higher education to all regions. The reform created exogenous variation in the regional supply of higher education. Using the reform as an instrument, our estimation results show that polytechnic graduates have a 7.5 (13.7) percentage points higher migration probability during a three-year (six-year) follow-up period than vocational college graduates.
Keywords: J10; J61; I20; R23; 330; migration; higher education; vocational education; polytechnic education; school reform